Effects of increasing crystalline lysine with other amino acids on growth performance of 85- to 135-lb gilts - Main, R.G.; Usry, J.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 1,134 gilts (each initially 85 lb, PIC L337 x C22) was used in a 28-d experiment to evaluate the effects of replacing soybean meal with up to 8 lb/ton of crystalline Llysine HCl with other crystalline amino acids on growth performance. Gilts were randomly allotted to one of six experimental diets. Diets were corn-soybean meal-based with 3% added fat. Diets included a negative control containing 3 lb/ton of L-lysine HCl and formulated to 0.90% true ileal digestible lysine. Two additional diets were formulated with 3 lb/ton Llysine to 1.0% true ileal digestible lysine but with or without crystalline threonine and methionine to compare threonine to lysine ratios of 60 versus 65% and methionine & cystine (TSAA) ratios of 55 vs. 60%. The three remaining diets contained 6, 7, or 8 lb/ton of Llysine HCl with crystalline threonine and methionine to provide the same ratios relative to lysine of 65 and 60%, respectively. Pigs fed the negative control diet (0.90 true ileal digestible lysine) had decreased ADG, poorer F/G, and were lighter at then end of the trial than pigs fed the diet containing 3 lb/ton L-lysine with added L-threonine and DL methionine (P<0.05). This indicates that diets containing 1.0% true ileal digestible lysine were not over the pigs’ lysine requirement. Pigs fed 1.0% true ileal digestible lysine with high threonine and TSAA ratios (65 and 60% relative to lysine, respectively) had similar ADG but tended to have better (P<0.08) F/G than those fed the lower threonine and TSAA ratios. Using 6, 7, or 8 lb/ton of Llysine HCl with added threonine and methionine in diets formulated to 1.0% true ileal digestible lysine had no effect on ADG or F/G, but did tend to decrease ADFI (linear, P<0.04; quadratic P<0.07). These results suggest that the use of up to 8 lb/ton of L-lysine HCl in conjunction with L-threonine and DL methionine to maintain proper amino acid to lysine ratios will not negatively affect pig performance. In addition, increasing the true ileal digestible threonine:lysine (60 to 65%) and TSAA:lysine ratios (55 to 60%) improved F/G in this experiment.
Keywords: Crystalline amino acids; Growing pigs; Performance; Swine